The case of Pelagie Inuk: The only Inuk woman to become a Grey Nun - Laugrand, Frédéric; Oosten, Jarich (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2014)
In the Arctic, no studies have been made of Indigenous nuns. In this paper we present the case of Pelagie Inuk, who became a Grey Nun. Motivated by a wish to help other people, Pelagie chose the celibate life of a Grey Nun, instead of a married life in an Inuit family. The missionaries often presented her as a role model who took the right path in contrast to other individuals who clung to their “pagan,” i.e. shamanic traditions, but her life history shows that she remained caught between conflicting traditions and finally opted for life in an Inuit family.